My First Words Picture Cards - Yorke,Jane (London D.K. Publishing, 2018)
Give your toddler a head start with 16 colourful flashcards, expertly designed to develop early language skills and ideal for preschool play. With a vibrant image on every flashcard, DK's My first Words sturdy picture cards make learning first words fun. Talking points on the back of each card reinforce learning, helping to familiarise children with the shape, colour and sound of each object, from keys to the colourful ball. There is an additional card for parents with tips for creative learning games for you and your little one to share. With a range of popular early learning topics for young children, including My First Animals Picture Cards, My First Colours and Shapes Picture Cards, My First Farm Picture Cards, My First Numbers and Counting Picture Cards, and My First Things That Go Picture Cards choose the perfect picture card pack for you and your toddler. Each card has a touch and feel area and the set includes: dog, teddy bear, baby, keys, tractor, car, fire truck, ball, fish, cat, corn, apple, mirror, shoes, jam, jumper
Keywords: Flashcards